A New Method of Subretinal Injection of Tissue Plasminogen Activator and Air in Patients With Submacular Hemorrhage. Issue 8 (August 2017) - Novelli, Fernando J. D.; Preti, Rony C.; Monteiro, Mario L. R.; Nóbrega, Mario J.; Takahashi, Walter Y.
Abstract : Supplemental Digital Content is Available in the Text.